Better principals, better schools : what star principals know, believe, and do - Stafford, Delia; Hill-Jackson, Valerie; Hartlep, Nicholas D.; Chapman, Thandeka (Urban education study series, 2016)
A school is only as good as its principal'. This quip forms the thesis of Better Principals as it provides a bird's eye view on the enactment of Haberman's eleven core functions of a star principal. Better Principals is imperative for two main reasons. First, the achievement gap between 20 million children in poverty and their mainstream counterparts is continuing to become even wider. Many students are constantly subjected to inequality of educational opportunity, which limits their future opportunities. Second, Haberman is one of the most prolific producers of administrators of the twentieth century (and into the twenty-first century). He reminds us that quality school systems, with quality leaders, benefit our society. Haberman explained that there is often selection blindness when it comes to identifying school leaders, and this deficiency has many negative consequences for education in general, and learners in particular. Haberman has generated theories, training programs and tools to engender substantive changes needed to produce better schools. Each chapter in this volume contains reflection questions for discussion to remind us all why selecting quality principals must be paramount when hiring school leaders. These illustrative book chapters emphasize the execution of Haberman's star principal ideology.